Changes in retinal vascular geometry after vitrectomy in idiopathic and uveitic epiretinal membrane - Chang Hwan Lee; Seung Woo Choi; Eun Kyoung Lee; Chang Ki Yoon; Un Chul Park; Kyu Hyung Park; Sojung Go; Sang Jun Park; Kunho Bae (Scientific Reports)
Abstract Epiretinal membrane (ERM) can arise idiopathically or secondary to uveitis, each driven by distinct pathophysiological mechanisms. Because ERMs exert tractional forces that distort both the retina and its vasculature, vascular geometry can serve as an indirect marker of the tractional forces acting on the retina. This study aimed to evaluate the associations between postoperative changes in retinal vascular geometry and functional outcomes in patients with idiopathic and uveitic epiretinal membrane (iERM and uERM). A retrospective analysis was performed on 72 eyes (42 iERM, 30 uERM) that underwent pars plana vitrectomy for ERM. Retinal vascular geometric parameters, including arterial and venous angles, branching angles, and tortuosity, were quantitatively measured using conventional retinal fundus photographs. Best-corrected visual acuity (BCVA) and central foveal thickness (CFT) were measured preoperatively and at 1 and 6 months postoperatively. The primary outcome was the comparison of postoperative changes in retinal vascular geometry between iERM and uERM, while the secondary outcome assessed improvements in BCVA, M-score, and CFT, and their correlation with vascular changes. Greater postoperative changes in arterial angle were significantly associated with improvements in BCVA and CFT. The iERM group exhibited more pronounced changes in retinal vascular geometry than the uERM group, particularly in branching venous angles and venous tortuosity. These differences became more evident over time. In conclusion, this study demonstrates that postoperative changes in retinal vascular geometry differ between patients with iERM and uERM, with more significant changes observed in iERM. These findings provide valuable insight into the distinct recovery mechanisms in iERM and uERM, emphasizing the roles of tractional forces and inflammation in shaping postoperative outcomes.